Pertanggungjawaban Produk (Product Liability) sebagai Salah Satu Alternatif Perlindungan Konsumen - Liya Sukma (Dialogia Iuridica, 2016)
Law No 8 of 1999 on Consumer Protection regulate product liability as a kind of form liability of businesses man in terms of compensation for the damage, pollution and consumer loss due to the consumption of either produced or traded goods. Burden of proof to denote elements of faults exist or not is hold by businesses man. Main issue of this research is to know how producers liability on its products to consumers. Meanwhile, this research goal is to seek application of liability product principle to protect consumer from harms made by businesses man. This research used juridical-normative methodology with descriptive analysis.